1994
DOI: 10.1161/01.res.75.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and tissue-specific regulation of rabbit skeletal and cardiac muscle calcium channels involved in excitation-contraction coupling.

Abstract: Two types of calcium channels signal excitation-contraction (E-C) coupling in striated muscle: dihydropyridine receptors (DHPRs, voltage-gated L-type calcium channels on the transverse tubule) and ryanodine receptors (RyRs, calcium release channels on the sarcoplasmic reticulum). Sarcolemmal depolarization activates the DHPR; subsequently, the RyR is activated and releases calcium that activates muscle contraction. We show in the present study that expression of the E-C coupling calcium channels is upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 53 publications
4
32
0
1
Order By: Relevance
“…rDHPR-C1 encodes the II-S6 region of the rat heart DHP receptor ␣ 1 subunit and is 92% identical to the published rabbit sequence. Northern hybridizations using heart DHP receptor ␣ 1 subunit cDNA probes typically identify three mRNAs in rabbit and mouse, ‫ف‬ 8, 9.5, and 22 kb (7,18,19). In the rabbit all three mRNAs are regulated coordinately during development (18).…”
Section: Methodsmentioning
confidence: 99%
“…rDHPR-C1 encodes the II-S6 region of the rat heart DHP receptor ␣ 1 subunit and is 92% identical to the published rabbit sequence. Northern hybridizations using heart DHP receptor ␣ 1 subunit cDNA probes typically identify three mRNAs in rabbit and mouse, ‫ف‬ 8, 9.5, and 22 kb (7,18,19). In the rabbit all three mRNAs are regulated coordinately during development (18).…”
Section: Methodsmentioning
confidence: 99%
“…None of these proteins were detected in undifferentiated C2C12 myoblasts (Fig. 1C, lane 1); up-regulation of the ␣ 1S subunit during skeletal muscle development has been established (45,46). The anti-sorcin antibody immunoprecipitated only the most slowly migrating form that was detected in myotubes, while lower M r forms that were reactive with SKN were not recovered (Fig.…”
Section: Sorcin Antibodymentioning
confidence: 95%
“…the ␣ 1C subunit increased by 2-3 fold between the perinatal period and adulthood (33). In contrast to rabbit, Ca current density in cultured rat neonatal myocytes is much greater than in acutely isolated rat adult myocytes (34).…”
mentioning
confidence: 86%
“…Inhibition of this Ca influx would be expected to adversely affect the fetal heart. It has been suggested that during fetal and neonatal stages, when expression of L-type Ca channels involved in EC-coupling is low, small doses of Ca channel blockers could have adverse effects on the myocardium (33). A Ca channel blocking effect could result in diminished cardiac contractility.…”
mentioning
confidence: 99%